2015
DOI: 10.1007/s00134-015-4125-2
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic dysfunction in patients with ICU-acquired weakness and its impact on extubation failure

Abstract: Diaphragm dysfunction is frequent in patients with ICU-acquired weakness (80 %) but poorly correlated with the ICU-acquired weakness MRC score. Half of the patients with ICU-acquired weakness were successfully extubated. Half of the patients who failed the weaning process died during the ICU stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
210
3
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 243 publications
(242 citation statements)
references
References 49 publications
3
210
3
18
Order By: Relevance
“…In a previous study, diaphragm dysfunction in ICU‐AW patients was observed in 80% of patients, and 50% had a failed extubation and died during the ICU stay 6. A range of 18‐69 hours of complete diaphragmatic inactivity and MV support results in marked diaphragm myofiber atrophy 7.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study, diaphragm dysfunction in ICU‐AW patients was observed in 80% of patients, and 50% had a failed extubation and died during the ICU stay 6. A range of 18‐69 hours of complete diaphragmatic inactivity and MV support results in marked diaphragm myofiber atrophy 7.…”
Section: Discussionmentioning
confidence: 96%
“…For the first time, it was shown that patient-ventilator asynchrony was detected in all patients and in all ventilator modes, and was associated with mortality [14]. Reducing the incidence of asynchrony is crucial in optimizing the patient for extubation, which must be considered even in patients with ICU-acquired weakness: researchers reported that half of all patients with ICU-acquired weakness were successfully extubated [15]. The ability to identify such patients, however, remains elusive.…”
Section: New Parameters For Monitoring Invasive Mechanical Ventilationmentioning
confidence: 99%
“…ICU-acquired weakness-both myopathy and neuropathy [15]-is associated with delayed weaning from mechanical ventilation [1]. One study [15] investigated whether ICU-acquired weakness was associated with diaphragm dysfunction, using a multimodal tool combining magnetic stimulation of the phrenic nerves, diaphragm ultrasound, and pulmonary function tests to evaluate diaphragmatic function at the bedside. Diaphragm dysfunction was frequent in patients with ICUacquired weakness (80%), but correlated poorly with the ICU-acquired weakness Medical Research Council score.…”
Section: Liberation From Invasive Mechanical Ventilation: Don't Be Shy!mentioning
confidence: 99%
See 1 more Smart Citation
“…Bu noktada diyafragma karaciğerin hemen üzerinde görece olarak non-ekojenik üç katmanlı bir kas yapısı olarak gözükmektedir. Diyafragma kalınlaşması M-modda ekspiryum sonu kalınlık ve inspiryum sonu kalın-lık olarak ölçülmekte ve diyafragma kalınlık fraksiyonu (inspiryum sonundaki kalınlık -ekspiryum sonundaki kalınlık / ekspiryum sonundaki kalınlık) ve yüzde olarak ifade edilmektedir (4,7). Kullanımının yaygınlaş-ması özellikle YBÜKG olan hastalarda weaning yönetiminde yol gösteri-ci olabilir.…”
Section: Yorumunclassified